2020
DOI: 10.1093/biolre/ioaa139
|View full text |Cite
|
Sign up to set email alerts
|

Age-related alterations in fertilization-induced Ca2+ oscillations depend on the genetic background of mouse oocytes†

Abstract: Maternal aging affects various aspects of oocytes’ physiology, including the functionality of their nuclear apparatus and mitochondria. In the present paper, we wished to investigate whether advanced reproductive age impacts also oocytes’ ability to generate proper Ca2+ oscillations in response to monospermic fertilization. We examined three different mouse strains/crosses: inbred C57BL/6Tar, outbred Tar:SWISS, and hybrid F1 (C57BL/6Tar x CBA/Tar). The females were either 2–4 months old (young) or 13–16 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
2
1
0
Order By: Relevance
“…These data therefore indicate that NEBD is complete in bovine zygotes and that NE remnants do not appear to contribute to spatial separation of parental genomes or dual spindle formation. The diffuse distribution of calnexin signal in bovine zygotes closely resembles previously published ER labeling data in oocytes and zygotes of other mammalian species, including human ( FitzHarris et al, 2007 ; Payne and Schatten, 2003 ; Audouard et al, 2011 ; Czajkowska et al, 2020 ; Balakier et al, 2002 ; Hölzenspies et al, 2009 ). Our data demonstrate that ER does not form a physical barrier within the metaphase spindle between proximate parental genomes (maximum intensity projections across whole spindle volumes, Fig.…”
Section: Resultssupporting
confidence: 85%
“…These data therefore indicate that NEBD is complete in bovine zygotes and that NE remnants do not appear to contribute to spatial separation of parental genomes or dual spindle formation. The diffuse distribution of calnexin signal in bovine zygotes closely resembles previously published ER labeling data in oocytes and zygotes of other mammalian species, including human ( FitzHarris et al, 2007 ; Payne and Schatten, 2003 ; Audouard et al, 2011 ; Czajkowska et al, 2020 ; Balakier et al, 2002 ; Hölzenspies et al, 2009 ). Our data demonstrate that ER does not form a physical barrier within the metaphase spindle between proximate parental genomes (maximum intensity projections across whole spindle volumes, Fig.…”
Section: Resultssupporting
confidence: 85%
“…Different mouse strains have different properties in Ca 2+ storage area and the post-fertilization (32,34). Our results demonstrated that calcium channels might enhance the parthenogenetic embryo development in certain mouse strains consistent with previous reports (30)(31)(32)34).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, during the late phase, none of the tested genes was significantly affected by diet despite the continued increase in weight gain and hypercholesterolemia. This could be due to the advanced age of the mice at this time point and the relatively shorter reproductive lifespan of the B6 compared to Swiss mice [ 80 ].…”
Section: Discussionmentioning
confidence: 99%